Trade Policy, Trade Volumes, and Plant-Level Productivity in Colombian Manufacturing Industries - Fernandes, Ana Margarida (World Bank, Washington, DC, 2014)
Fernandes explores Colombian trade policy from 1977-91, a period of substantial variation in protection across industries, to examine whether increased exposure to foreign competition generates plant-level productivity gains. Using a large panel of manufacturing plants, she finds a strong positive impact of tariff liberalization on consistent productivity estimates, controlling for plant and industry heterogeneity. This result is not driven by the endogeneity of protection nor by plant exit. The impact of tariff liberalization on productivity is stronger for large plants and for plants in less competitive industries. Qualitatively similar results are obtained when using effective rates of protection and import penetration ratios as measures of protection